Targeting activation of specific NF-[kappa]B subunits prevents stress-dependent atherothrombotic gene expression - Djuric, Zdenka; Kashif, Muhammed; Fleming, Thomas; Muḥammad, Sajjad; Piel, David; Bauer, Rüdiger von; Bea, Florian; Herzig, Stephan; Zeier, Martin; Isermann, Berend; Hecker, Markus; Schwaninger, Markus; et al. (Molecular medicine, 2012)
Psychosocial stress has been shown to be a contributing factor in the development of atherosclerosis. Although the underlying mechanisms have not been elucidated entirely, it has been shown previously that the transcription factor nuclear factor-κB (NF-κB) is an important component of stress-activated signaling pathway. In this study, we aimed to decipher the mechanisms of stress-induced NF-κB-mediated gene expression, using an in vitro and in vivo model of psychosocial stress. Induction of stress led to NF-κB-dependent expression of proinflammatory (tissue factor, intracellular adhesive molecule 1 [ICAM-1]) and protective genes (manganese superoxide dismutase [MnSOD]) via p50, p65 or cRel. Selective inhibition of the different subunits and the respective kinases showed that inhibition of cRel leads to the reduction of atherosclerotic lesions in apolipoprotein−/− (ApoE−/−) mice via suppression of proinflammatory gene expression. This observation may therefore provide a possible explanation for ineffectiveness of antioxidant therapies and suggests that selective targeting of cRel activation may provide a novel approach for the treatment of stress-related inflammatory vascular disease.